Photoluminescence of AlxGa1 − xP еpitaxial layers grown by liquid-phase epitaxy method - Brinkevich, Dmitrii I.; Odzhaev, Vladimir B.; Prasalovich, Uladislau S.; Yankovski, Yurii N.; Kenzhaev, Zoir T.; Ismaylov, Bayrambay K. (Journal of the Belarusian State University. Physics, 2026)
AlxGa1 − xP epitaxial layers (x = 0.06 – 0.61) grown on GaP substrates by crystallisation from indium-based melt-solutions in the temperature interval of 975 – 950 °С were investigated. The thickness of layers varied in the range of 3 –19 μm. Elemental analysis was made using local X-ray probe microanalysis. Measurement of the photoluminescence spectra at temperature of 4.2 K gave the following results. A number of bands were observed in the range of 2.0 –2.4 eV in all spectra of the studied AlxGa1 − xP samples. With an increase in aluminium concentration, they shifted to the high-energy region. With an aluminium content in the melt-solution in the amount of 0.16 wt. %, the most intense band had a maximum at 549 nm, which corresponds to the green colour of the radiation. These bands were probably caused by the donor – acceptor pairs recombination. Doping of the epitaxial layers with zinc and magnesium was carried out by diffusion. GaP microparticles up to 4 μm in size were detected in the AlGaP epitaxial layers. The possibility of doping the AlGaP epitaxial layers with nitrogen by adding P3N5 to the melt was demonstrated. It was concluded that doping of AlxGa1 − xP epitaxial layers with nitrogen and sulfur occurs through autodiffusion of these impurities from the substrate due to their presence in GaP particles. Doping of AlGaP epitaxial layers with the rare-earth element gadolinium by introducing it into the melt-solution as well as doping these epitaxial layers with zinc by diffusion did not result in any changes in the photoluminescence spectra in the range of 2.0 –2.4 eV. The broad intensive band with maximum near 1.99 eV was observed in AlGaP epitaxial layers doped with magnesium by diffusion. It was established that noticeable contamination of AlxGa1 − xP epitaxial layers with oxygen during liquid-phase epitaxy is absent. Changes in photoluminescence caused by radiative recombination on deep defects and impurities introduced into the layers during various processing stages were analysed.